St. Agnes' stand - Eidson, Tom (Thorndike, Me. : Thorndike Press, 1994)
When Nat Swanson, a cowboy on the run, stumbles across the trapped survivors of an Indian Apache ambush, the last thing he imagines is that he will be trying to save the lives of three nuns and seven children. Sister St Agnes is convinced he has been sent by God.
68678
Keywords: Apache Indians -- Fiction. -- Wars, 1883-1886; Orphans -- Fiction. -- New Mexico; Nuns -- Fiction. -- New Mexico; Large type books; New Mexico -- Fiction; Western stories